A model for the regulation of follicular dendritic cells predicts invariant reciprocal‐time decay of post‐vaccine antibody response. Issue 9 (26th September 2017) - Almudevar, Anthony
Abstract : Follicular dendritic cells (FDC) play a crucial role in the regulation of humoral immunity. They are believed to be responsible for long‐term persistence of antibody, due to their role in antibody response induction and their ability to retain antigen in immunogenic form for long periods. In this article, a regulatory control model is proposed which links persistence of humoral immunity with cellular processes associated with FDCs. The argument comprises three elements. The first is a literature review of population‐level studies of post‐vaccination antibody persistence. It is found that reciprocal‐time (∝1/ t ) decay of antibody levels is widely reported, over a range of ages, observation times and vaccine types. The second element is a mathematical control model for cell population decay for which reciprocal‐time decay is a stable attractor. Additionally, control effectors are easily identified, leading to models of homeostatic control of the reciprocal‐time decay rate. The final element is a literature review of FDC functionality. This reveals a striking concordance between cell properties required by the model and those widely observed of FDCs, some of which are unique to this cell type. The proposed model is able to unify a wide range of disparate observations of FDC function under one regulatory principle, and to characterize precisely forms of FDC regulation and dysregulation. Many infectious and immunological diseases are increasingly being linked to FDC regulation, therefore a precise understanding of the underlying mechanisms would be of significant benefit for the development of new therapies.